Dressed in black. A New Ansonia Stoliczka, 1870 (Lissamphibia: Anura: Bufonidae) from Gunung Murud, Sarawak, East Malaysia (Borneo) - Hertwig, Stefan T.; Min, Pui Yong; Haas, Alexander; Das, Indraneil (Zootaxa, 2014)
A new species of stream toad of the genus Ansonia is described from Gunung Murud, Pulong Tau National Park, of northern Sarawak, Malaysia, Borneo. Ansonia vidua, sp. nov., is morphologically distinguished from its Bornean congeners by the following combination of characters: medium size (SVL of adult females 33.5–34.4 mm); body uniformly black-brown in life; absence of a visible pattern on dorsum or limbs; presence of two low interorbital ridges; shagreened skin on dorsum, sides and upper surfaces of the limbs with numerous homogeneously small, rounded warts; first finger shorter than second; reduced webbing between the toes and an absence of a sharp tarsal ridge. Uncorrected genetic distances between related taxa of > 4.3% in 16S rRNA gene support its status as a hitherto undescribed species.